2018
DOI: 10.2478/s11756-018-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold stratification on seed germination in Solidago × niederederi (Asteraceae) and its parental species

Abstract: In this study, we investigated the influence of cold stratification on seed germination in S. × niederederi, a hybrid between the North American S. canadensis and the European S. virgaurea, using fruit samples collected in 2016 in Poland. We aimed to test the hypothesis that the low temperature exposure decreases the final percentage and speed of seed germination in the hybrid and its parental species. For each species, sets of 100 achenes in three replications were mixed with dry sand and stored in Petri dish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…worth mentioning that in other seed germination tests, in which the sand was used as a substrate (Pliszko and Kostrakiewicz-Gierałt 2017a, 2017b, 2018a, the percentage of germinated seeds of the hybrid was higher than that achieved on filter paper in this study. However, the percentage of germinated seeds could be also affected by genetic differences between the hybrid populations from which the fruits have been sampled.…”
Section: Taxoncontrasting
confidence: 57%
See 2 more Smart Citations
“…worth mentioning that in other seed germination tests, in which the sand was used as a substrate (Pliszko and Kostrakiewicz-Gierałt 2017a, 2017b, 2018a, the percentage of germinated seeds of the hybrid was higher than that achieved on filter paper in this study. However, the percentage of germinated seeds could be also affected by genetic differences between the hybrid populations from which the fruits have been sampled.…”
Section: Taxoncontrasting
confidence: 57%
“…Similarly, Gudžinskas and Žalneravičius (2016) evidenced significant differences in the length of pappus between S. gigantea and S. virgaurea. Until now, seed germination of S. ×niederederi was tested using the fruits with intact pappus (Pliszko and Kostrakiewicz-Gierałt 2017a, 2017b, 2018a. In this study, we demonstrated that seed germination of the hybrid occurs in fruits with removed pappus as well.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our interest in this field concerns the chemistry of lead(II) [ 10 , 11 , 12 , 13 , 14 ] and bismuth(III) coordination polymers with heteroaromatic carboxylate ligands. When selecting a central ion, we focused on the multiple applications of Bi(III) compounds as, for example, photoluminescent materials [ 15 , 16 , 17 ], catalysts [ 18 ], medical drugs for gastrointestinal disorders caused by Helicobacter pylori or anticancer agents [ 19 , 20 , 21 , 22 ]. Furthermore, the Bi(III) ion exhibits a [Xe]4 f 14 5 d 10 6 s 2 ground state electronic configuration and belongs to a group of metal ions (Tl(I), Pb(II), Sn(II), Sb(III)) possessing a lone electron pair (n s 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its reduced pollen viability, S. ×niederederi can produce a low number of fruits (cypselas) with viable seeds (Migdałek et al 2014, Karpavičienė & Radušienė 2016, Pliszko & Kostrakiewicz-Gierałt 2017. Moreover, the seeds of S. ×niederederi germinate easily with no involvement of cold stratification (Pliszko & Kostrakiewicz-Gierałt 2018) and even if their pappus is removed from the fruit (Pliszko & Kostrakiewicz-Gierałt 2020). In contrast, the development of fruits in S. ×snarskisii has not been observed so far suggesting its sterility (Gudžinskas & Žalneravičius 2016, Pliszko 2018).…”
Section: Introductionmentioning
confidence: 99%